PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA SEKOLAH DASAR - Syalsa Riski Maulina; Fadhilaturrahmi; Nurhaswinda; Rusdial Marta; Mufarizuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this study is the low mathematical representation ability of students in mathematics in grade V. This study aims to improve the mathematical representation ability of students in grade V at UPT SDN 010 Siabu. This study is a classroom action research, which was conducted in two cycles, with each cycle consisting of two meetings. The subjects in this study were 13 fifth-grade students. The data collection techniques used in this study were observation, tests, and documentation. The research instruments were observation sheets of teacher and student activities, written tests, and project assessment rubrics. Meanwhile, the data analysis techniques used were qualitative data analysis and quantitative data analysis. The results of the study show that the application of the Project Based Learning model can improve students' mathematical representation skills, which before the intervention only reached 31% in the very low category. After cycle I, it reached 54% in the very low category and increased in cycle II to 84.6% in the good category. Thus, it can be concluded that using the Project Based Learning model can improve students' mathematical representation skills in mathematics learning at UPT SDN 010 Siabu